Health-Related Quality of Life as Measured by the 36-Item Short Form Survey Among Adults With Acute Bacterial Skin and Skin Structure Infections who Received Either Omadacycline or Linezolid in a Phase 3 Double-Blind, Double-Dummy Clinical Trial. (8th September 2021) - Chitra, Surya; Hinahara, Jordan; Goss, Thomas F; Gunter, Kyle; LaPensee, Kenneth
Abstract: This analysis of data from a Phase 3 study of adults with acute bacterial skin and skin structure infections showed that successful oral treatment with omadacycline (n = 368) or linezolid (n = 367) was associated with improvement in health-related quality of life.